A novel interaction between CX3CR1 and CCR2 signalling in monocytes constitutes an underlying mechanism for persistent vincristine-induced pain - Karli Montague; Raffaele Simeoli; Joao Valente; Marzia Malcangio (Journal of Neuroinflammation, 2018)
Abstract Background A dose-limiting side effect of chemotherapeutic agents such as vincristine (VCR) is neuropathic pain, which is poorly managed at present. Chemokine-mediated immune cell/neuron communication in preclinical VCR-induced pain forms an intriguing basis for the development of analgesics. In a murine VCR model, CX3CR1 receptor-mediated signalling in monocytes/macrophages in the sciatic nerve orchestrates the development of mechanical hypersensitivity (allodynia). CX3CR1-deficient mice however still develop allodynia, albeit delayed; thus, additional underlying mechanisms emerge as VCR accumulates. Whilst both patrolling and inflammatory monocytes express CX3CR1, only inflammatory monocytes express CCR2 receptors. We therefore assessed the role of CCR2 in monocytes in later stages of VCR-induced allodynia. Methods Mechanically evoked hypersensitivity was assessed in VCR-treated CCR2- or CX3CR1-deficient mice. In CX3CR1-deficient mice, the CCR2 antagonist, RS-102895, was also administered. Immunohistochemistry and Western blot analysis were employed to determine monocyte/macrophage infiltration into the sciatic nerve as well as neuronal activation in lumbar DRG, whilst flow cytometry was used to characterise monocytes in CX3CR1-deficient mice. In addition, THP-1 cells were used to assess CX3CR1-CCR2 receptor interactions in vitro, with Western blot analysis and ELISA being used to assess expression of CCR2 and proinflammatory cytokines. Results We show that CCR2 signalling plays a mechanistic role in allodynia that develops in CX3CR1-deficient mice with increasing VCR exposure. Indeed, the CCR2 antagonist, RS-102895, proves ineffective in mice possessing functional CX3CR1 receptors but reduces VCR-induced allodynia in CX3CR1-deficient mice, in which CCR2 + monocytes are elevated by VCR. We suggest that a novel interaction between CX3CR1 and CCR2 receptors in monocytes accounts for the therapeutic effect of RS-102895 in CX3CR1-deficient mice. Indeed, we observe that CCR2, along with its ligand, CCL2, is elevated in the sciatic nerve in CX3CR1-deficient mice, whilst in THP-1 cells (human monocytes), downregulating CX3CR1 upregulates CCR2 expression via p38 MAP kinase signalling. We also show that the CX3CR1-CCR2 interaction in vitro regulates the release of pronociceptive cytokines TNF-α and IL1β. Conclusions Our data suggests that CCL2/CCR2 signalling plays a crucial role in VCR-induced allodynia in CX3CR1-deficient mice, which arises as a result of an interaction between CX3CR1 and CCR2 in monocytes.